HUBUNGAN BERAT LAHIR BAYI DENGAN KEJADIAN RUPTUR PERINEUM PADA PERSALINAN NORMAL PRIMIPARA - Safitri M; Noviatri S; Cahyaningrum E (Universitas Harapan Bangsa Purwokerto, 2011)
Rupture of the perineum is a tear that occurs at birth either spontaneously or with atool or action .Based on research Puslitbang years 2009 - 2010 in several provinces in Indonesiafound that one in five mothers who have died of a ruptured perineum (20 %). Perineum ruptureslevel is the level of the perineum tear that occurs for some reason during delivery, especially inprimiparous, one reason is the birth weight. The incidence rupture of the perineum in normallabor primipara in Kebumen Hospital has increased which in 2010 amounted to 675 cases andin 2011 was 818 cases. Determine the relationship between birth weight infants with rupture of the perineum in normal labor primipara in Kebumen General Hospital in 2011. Descriptive study correlatesusing retrospective approach captured data is birth weight infants with rupture of the perineumin normal labor primipara in hospitals Kebumen in 2011, the population in this study were allbirth mothers primiparous totaled 922 mothers, the sampling technique total sampling, retrievalmaster data using tables, with data analysis using chi-square. There is a relationship between birth weight infants with rupture of the perineum innormal labor primipara in Kebumen General Hospital in 2011. Keywords: birth weight babies, rupture perineum, normal childbirth, primipara